Relapsed cervicomediastinal lymph node carcinoma with an unknown primary site treated with TS-1 alone: a case report - Yajima, Toshiki (BioMed Central, 2013)
BACKGROUND: Cervicomediastinal lymph node carcinoma with an unknown primary site is quite rare, and useful treatment of these diseases has not been established. We report here the case of a patient successfully treated with TS-1 alone after the relapse of cervicomediastinal lymph node carcinoma with an unknown primary site. CASE PRESENTATION: A 62-year-old man was referred to our hospital because of cervicomediastinal lymph node swelling and high serum levels of carbohydrate antigen 19-9 and carcinoembryonic antigen. Fluorodeoxyglucose-positron emission tomography/computed tomography revealed an accumulation of fluorodeoxyglucose in the left supraclavicular lymph nodes, mediastinal lymph nodes, and the pelvic cavity. Colonoscopy revealed rectal cancer, which was diagnosed by biopsy as a tubular adenocarcinoma. Because metastases from rectal cancer to the cervicomediastinal lymph nodes are rare, the patient underwent thoracoscopic mediastinal lymphadenectomy. A biopsy specimen from the paraaortic lymph nodes demonstrated papillary adenocarcinoma that was pathologically different from the rectal cancer; therefore, a diagnosis of mediastinal carcinoma with an unknown primary site was established. The patient underwent low anterior resection of the rectum for the rectal cancer, and no abdominal lymph node metastasis (pMP, N0/stage I) was found. Although radiotherapy was performed for the cervicomediastinal lymph nodes, the mediastinal carcinoma relapsed after 6 months. Because the patient desired oral chemotherapy on an outpatient basis, TS-1 was administered at a dosage of 80 mg/day for 2 weeks, followed by a 1-week rest. TS-1 treatment resulted in a decrease in the size of the cervicomediastinal lymph nodes, and the serum tumor marker levels decreased to normal after the fourth course. The patient continued TS-1 treatment without adverse events and is currently alive without recurrence or identification of the primary site at the 32nd month after TS-1 treatment. CONCLUSION: This is the first reported case of relapsed cervicomediastinal lymph node carcinoma with an unknown primary site treated by TS-1 alone. TS-1 treatment for the carcinoma with an unknown primary site may be useful in patients who are not candidates for systemic platinum-based chemotherapy.